Clinical significance of cerebrospinal fluid soluble CD25 in pediatric hemophagocytic lymphohistiocytosis with central nervous system involvement. Issue 8 (20th April 2022) - Ou, Wenxin; Ma, Honghao; Wei, Ang; Zhao, Yunze; Zhang, Liping; Lian, Hongyun; Zhang, Qing; Chen, Sitong; Wang, Dong; Li, Zhigang; Zhang, Rui; Wang, Tianyou
Abstract: Objective: To analyze the clinical significance of soluble CD25 (sCD25) levels in cerebrospinal fluid (CSF) in pediatric hemophagocytic lymphohistiocytosis (HLH) with central nervous system (CNS) involvement. Methods: All patients diagnosed with HLH admitted to Beijing Children's Hospital, Capital Medical University between January 1, 2017 and October 31, 2021 who received a measurement of their HLH‐related parameters and CSF sCD25 levels at admission were enrolled in this study. Results: CSF sCD25 levels in patients with primary HLH were higher than those in patients with Epstein–Barr virus infection‐associated HLH, and the median level was 444 pg/ml. The difference in CSF sCD25 levels between the non‐CNS group and the CNS group was statistically significant (591 [259–33, 643] pg/ml vs. 123 (36–437) pg/ml, p < .001). The best cutoff value of CSF sCD25 was 273.5 pg/ml (AUC = 0.987, 95% CI: 0.972–1.000), with sensitivity, specificity, positive predictive values, and negative predictive values of 96.4%, 92.8%, 81.8%, and 98.7%, respectively. CSF sCD25 in the severe CNS involvement group was significantly higher than that in the nonsevere CNS involvement group ( p = .014). The 3‐year overall survival (OS) of patients with high CSF sCD25 levels was lower than that of patients with low CSF sCD25 levels(71.6% ± 8.1% vs. 93.3% ± 2.9%, hazard ratio [HR] = 3.637, p = .003). Conclusion: Increased CSF sCD25 levels in active disease can predict CNS‐HLH. Primary HLH has a higher CSF sCD25 level than Epstein–Barr virus infection‐associated HLH. Patients who are diagnosed with CNS‐HLH with CSF sCD25 levels higher than 273.5 pg/ml are more likely to develop severe CNS involvement, suggesting a poor prognosis.